Housed feeding improves rumen health by influencing the composition of the microbiota in Honghe cattle - Fu, Runqi; Han, Lin; Jin, Chunjia; Yu, Ye; Fu, Binlong; Li, Qian; Leng, Jing (Frontiers in Veterinary Science, 2025)
Rumen is one of the most vital organs for the digestion of ruminants and is influenced by factors including feeding patterns and nutrition. How rumen microbiota and barrier function change are affected feeding patterns requires attention, particularly for beef cattle. In the present study, the Honghe cattle under grazing (CON group, n = 10) and housed feeding (HES group, n = 10) conditions were selected as a model of different rumen microbiota and observed for 180 days. The indicators of immunity and antioxidants in serum and rumen epithelium of cattle were measured; and the rumen microbiota were evaluated by using 16S rRNA and ITS sequencing techniques. In the present study, the concentrations of total protein, albumin and glucose in serum of Honghe cattle were significantly increased by the HES group when compared with CON group (p < 0.05). The HES group reduced the levels of complement 3, complement 4, interleukin-4, interleukin-10, interleukin-1β and tumor necrosis factor α, but increased the levels of total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) (p < 0.05). We found that the HES group enhanced the levels of T-AOC and SOD in rumen epithelium (p < 0.05). Furthermore, there was a significant up-regulation of the relative mRNA expressions of ZO-1, OCC, SOD1, SOD2, Nrf2, NQO-1 and HO-1 observed in the HES group (p < 0.05). For rumen microbiota, the HES group significantly decreased alpha diversity. The core rumen bacterial communities were Bacteroidata, Firmicutes and Proteobacteria. The relative abundances of Prevotella and Ruminococcus were increased by the HES group, but norank_f_Bacteroidales_UCG-001, Rikenellaceae_RC9_gut_group and Prevotellaceae_UCG-003 were decreased (p < 0.05). Moreover, The HES group enhanced the relative abundance of Pichia, Cyllamyces, Sterigmatomyces and Wallemia (p < 0.05), but decreased Aspergillus and Candida (p < 0.05). There was a positive correlation between microorganisms such as Prevotella, Ruminococcus and Pichia and rumen epithelial barrier and antioxidant-related genes (p < 0.05). Overall, housed feeding contributed to the improvement of antioxidant capacity and rumen health in Honghe cattle, which may be related to the modulation of rumen microbiota including bacteria and fungi.